Acupuncture decreased the risk of coronary heart disease in patients with rheumatoid arthritis in Taiwan: a Nationwide propensity score-matched study - Mei-Yao Wu; Ming-Cheng Huang; Hou-Hsun Liao; Jen-Huai Chiang; Yu-Chen Lee; Chung-Y Hsu; Mao-Feng Sun; Hung-Rong Yen (BMC, 2018)
Abstract Background Patients with rheumatoid arthritis (RA) have a higher risk of coronary heart disease (CHD). Acupuncture, a commonly used treatment for patients with RA, has not been reported to prevent CHD in patients with RA. We aimed to assess the risk of developing CHD in acupuncture users and non-users of patients with RA. Methods We identified 29,741 patients with newly diagnosed RA from January 1997 to December 2010 from the Registry of Catastrophic Illness Patients Database from the Taiwanese National Health Insurance Research Database. Among them, 10,199 patients received acupuncture (acupuncture users), and 19,542 patients did not receive acupuncture (no-acupuncture users). After performing 1:1 propensity score matching by sex, age, baseline comorbidity, conventional treatment, initial diagnostic year, and index year, there were 9932 patients in both the acupuncture and no-acupuncture cohorts. The main outcome was the diagnosis of CHD in patients with RA in the acupuncture and no-acupuncture cohorts. Results Acupuncture users had a lower incidence of CHD than non-users (adjusted HR = 0.60, 95% CI = 0.55-0.65). The estimated cumulative incidence of CHD was significantly lower in the acupuncture cohort (log-rank test, p < .001). Subgroup analysis showed that patients receiving manual acupuncture of traditional Chinese medicine style, electroacupuncture, or combination of both all had a lower incidence of CHD than patients never receiving acupuncture treatment. The beneficial effect of acupuncture on preventing CHD was independent of age, sex, diabetes mellitus, hypertension, hyperlipidemia, and statins use. Conclusions This is the first large-scale study to reveal that acupuncture might have beneficial effect on reducing the risk of CHD in patients with RA. This study may provide useful information for clinical utilization and future studies.